Some new existence results of positive solutions for anisotropic variable exponent operator - Rafik Guefaifia; Salah Boulaaras; Rashid Jan (Boundary Value Problems)
Abstract This work investigates positive solutions for equations involving the anisotropic variable exponent operator, a mathematical framework critical in modeling nonstandard growth phenomena. By deriving new existence results, the study advances the understanding of nonlinear partial differential equations in anisotropic and variable exponent settings. These findings have significant implications for real-world applications, such as fluid dynamics, image processing, and material science, where variable growth conditions arise naturally. More specifically, the study employs methods from functional analysis to investigate the existence, nonexistence, and minimal solutions of certain anisotropic equations within the framework of generalized Sobolev spaces.